Low molecular weight phenols in cork stoppers - Pena-Neira, A; Hernández, T; GARCIA-VALLEJO, M C; Cadahía, E; de Simon, B F; Suarez, J A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1999)
In this work, we study the low molecular-weight polyphenols in cork stoppers obtained from commercial wine bottles and in samples taken at five stages of the cork stopper manufacturing process. The phenolic compounds (acids, aldehydes, and coumarins) were analyzed by high pressure liquid chromatography with photodiode array detector. The results were studied by statistical methods in order to determine the relationship among these compounds and their variability throughout the industrial processing. Discriminant analysis showed that the phenolic composition allows differentiation of each stage in the manufacture of cork stoppers and the different provenances of stoppers obtained from commercial wine bottles. The results showed wide variations in phenolic content among cork stoppers within each region and each winery.
Keywords: Cork; phenolic compounds; stopper manufacturing

Low molecular-weight phenolic compounds in natural and agglomerated cork stoppers - Pena-Neira, A; BartolomÉ, B; Cadahía, E; Hernández, T; Garcia-Vallejo, C; GONZALEZ-ADRADOS, J R; Suarez-Lepe, J A (SCIENCES DES ALIMENTS, 1999)
The low molecular-weight phenolic compounds in cork stoppers used for the closure of wine bottles are studied. Different phenolic acids (gallic, protocatechuic, vanillic, caffeic, ferulic and ellagic), aldehydes (protocatechuic, p-hydroxybenzoic, vanillin, ethylvanillin and coniferilic), and coumarins (aesculetin and scopoletin) were determined in natural cork stoppers (untreated and chlorine-bleached) and in agglomerated cork stoppers (unbleached and peroxide-bleached). The ketone 2,3-dihydroxy-1-guaiacylpropan-1-one and four ellagic-acid-type tannins were detected in natural stoppers. The amount of most of the phenolic compounds studied was higher in the natural cork stoppers than in agglomerated stoppers. In natural cork stoppers, an Increase in the content of caffeic and ferulic acids and vanillin was observed after chlorine bleaching. In agglomerated stoppers however, peroxide bleaching produced a decrease in the content of these same compounds.
Keywords: Cork; low molecular-weight phenolic; Stopper; stopper treatment